Metabolomics analysis of splenectomy of Nile tilapia (Oreochromis niloticus) reveals the spleen involved in regulating liver lipids and amino acids metabolism - Tao, Yixi; Du, Chunying; Jiang, Shanwen; Zhang, Siling; Feng, Jingyun; Miao, Xiaomin; Xu, Hao; Li, Yun (Frontiers in Marine Science, 2024)
The liver is essential for nutritional balance in fish, and liver damage in farmed fish often arises from factors like overfeeding, causing various health issues. Clinical observations indicate that liver diseases frequently involve spleen dysfunction, and there is evidence to suggest that the spleen has a significant impact on liver function. However, there has been no discussion on the role of the spleen in maintaining liver health in fish. To understand the role of fish spleen in liver metabolism, this study selected Nile tilapia (Oreochromis niloticus) as the experimental material and first established a tilapia splenectomy model. Various biochemical parameters of the liver and serum were measured, and the liver metabolism characteristics of the splenectomy group (SP group) and the sham operation group (SO group) were analyzed using metabolomics. After splenectomy, biochemical parameters of the liver and serum showed abnormalities, including significant increases in total cholesterol (T-CHO) and serum total bile acid (TBA) levels, alongside a significant decrease in liver TBA levels, suggesting impaired metabolic function and cholesterol deposition in the liver. Metabolomics analysis showed that metabolites such as lipids, lipid-like molecules, and organic acids and derivatives were differentially regulated between the SO and SP group. KEGG analysis showed that differential metabolites were enriched in lipid metabolism and amino acid metabolism. The metabolic pathway analysis of differential metabolites showed that after splenectomy, the low-activity urea cycle in the liver may accelerate lipid synthesis, while low concentrations of aromatic amino acids and taurine may inhibit lipid catabolism. These results indicate that after splenectomy, the liver metabolic capacity is impaired, which causes abnormal lipid metabolism by interfering with amino acid metabolism, making splenectomy tilapia liver at risk of liver disease, including cholesterol deposition, hepatic steatosis and nonalcoholic fatty liver disease (NAFLD). Our results show that the spleen is involved in regulating liver lipid and amino acid metabolism, and the spleen may interfere with lipid metabolism by regulating liver amino acid metabolism. Our data can provide support for further research on liver and spleen functions and the immune-nutrient metabolism mechanisms in fish, as well as new ideas for healthy fish farming.